CORRELATION ANALYSIS OF PROFITABILITY IN THE MANAGEMENT SYSTEM OF AGRICULTURAL ENTERPRISES ON THE BASIS OF SUSTAINABLE DEVELOPMENT - Liubov KOVALSKA; Svitlana ROGACH; Nina PETRUKHA; Nataliya MAMONTOVA; Oksana YURCHENKO; Svitlana DEREVIANKO; Olena KOLUMBET (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article considers the specifics of ensuring the efficiency of agricultural enterprises on the example of the Volyn region, Ukraine. The need to achieve the appropriate level of profitability as a criterion for the successful operation of agricultural enterprises is identified. The results of the activity of agricultural enterprises of the region according to the criteria of profitability and profitability are analyzed. The correlation-regression model for the definition of the key criteria which express the efficiency of functioning of the agricultural enterprises is constructed.